Shaping Participation : How Digital Platform Design Influences User Participation - März, Gabriel (Slovenia, 2025)
This paper provides an integrative perspective on the factors influencing platform participation, a key driver of platform success. Based on a structured literature review of 99 scholarly articles from leading journals, this study synthesizes insights from the strategic, technical, and economic perspectives on digital platform design and governance from a participant viewpoint. It develops a participant-centric model that outlines the major determinants of platform adoption and homing decisions, considering both monetary and non-monetary costs, opportunity costs, and perceived benefits. The model also captures the dynamics of network effects and their implications for platform value creation, emphasizing the importance of strategic resource orchestration and adaptation over time. By unifying diverse concepts and frameworks, the paper addresses the complexity of platform ecosystems and provides actionable insights for platform providers seeking to enhance participant engagement and long-term platform viability. It contributes to the academic discourse by offering a comprehensive reference for future research and practical guidance for effective platform design and management.
38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings